Сосуды с налепами в древностях эстиев (на материале могильника Lauth /Б. Исаково) - Кулаков, Владимир И. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
In the European archaeological science studying history ledges on funeral vessels of the Amber land of the Roman time the very short. More fixed consideration of funeral ceramics of Baltic and regions adjoining to it is necessary. It will allow to be convinced that the tradition of production of group of three ledges on ceramics Aestii isn't so unique for Baltic. The German influence on funeral ceramics of a burial ground of Lauth / B. Isakovo (Kaliningrad region) and, respectively, Sambia's other burial grounds, was realized in three ledges on a vessel and in characteristic signs of the vessels which are perfectly comparable to types of Wielbark ceramics on R. Wolągewicz. Mapping of types of ledges on vessels testifies to distribution to an era of the Roman influence traditional for Balts double ledges by the western part of the peninsula of Sambia (an ancestral home of culture of the West Baltic barrows), and the unary ledges which are directly going back to oldgermany tradition, are placed on a right bank of river of Paslęk, the conventional border between areas of Wielbark and sambian-natangian cultures, and in the central Sambia. Differently, vessels with unary ledges accurately mark penetration of the German ceramic traditions (certainly, together with groups of their carriers) on Sambia. It is obvious that the German newcomers attracted here with prospect of participation in production of amber and in amber trade, were not only Yutland's who have arrived by sea the inhabitants, but also part of neighbors – carriers of Wielbark culture.